INTERACTION BETWEEN JAVA AND AMERICAN CULTURE THROUGH MUSIC GROUP JOGJA HIPHOP FOUNDATION IN YOGYAKARTA - Ali Ridho; Thibburruhany Thibburruhany; Sutan Kumala Pontas; Muhammad Anshori (Jurnal Pemikiran Islam, 2023)
Interaction between cultures can basically be translated into various cultural policies that emphasise the reality of religion, plurality, and other cultures in society. Interaction of various cultures does not mean that people are forced to accept something new that does not exist in the context of their lives. However, the interaction process is expected to give birth to awareness of the two different groups to provide space for mutual understanding without radical (read: violent) rejection. The research uses a qualitative method - an exploration of scientific journals and online media that discuss Jogja Hip-Hop Foundation with a scientific approach to intercultural communication. The aim is to identify in depth how Jogja HipHop Foundation can bring acculturation values between Javanese and American cultures, and examine the interaction between Javanese and American cultures through the Hip-Hop music tradition represented by Jogja HipHop Foundation. The result is that the use of Javanese language by JHF aims to instil the principle of respect and the American cultural model, which is known to be identical with the worldly, is able to combine with the distinctive Javanese culture, and can be enjoyed by young people.